2013
DOI: 10.1002/jgrd.50151
|View full text |Cite
|
Sign up to set email alerts
|

Identification of marine and continental aerosol sources in Paris using high resolution aerosol mass spectrometry

Abstract: [1] Major summertime aerosol emission sources in Paris were assessed using a high resolution time-of-flight aerosol mass spectrometer (HR-ToF-AMS). The application of positive matrix factorization (PMF) to the highly mass and time-resolved AMS measurements allowed the identification of primary and secondary sources of organic (OA) and sulfate aerosols. Primary anthropogenic emissions contributed on average~27% (14.7% cooking, 12% traffic) to the total organic mass, while the major contribution to the organic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
171
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 178 publications
(210 citation statements)
references
References 90 publications
28
171
1
Order By: Relevance
“…Hourly PILS-IC mass concentrations of MSA (average of 21 ng m −3 ; lower than those measured in Paris; average of 122 ng m −3 ; Crippa et al, 2013) compared to Mace Head, Ireland and Erdemli, Turkey (shown in Fig. 12) did not correlate with any ATOFMS particle numbers or mass concentrations or with any other measurements over the whole sampling period.…”
Section: Msamentioning
confidence: 72%
“…Hourly PILS-IC mass concentrations of MSA (average of 21 ng m −3 ; lower than those measured in Paris; average of 122 ng m −3 ; Crippa et al, 2013) compared to Mace Head, Ireland and Erdemli, Turkey (shown in Fig. 12) did not correlate with any ATOFMS particle numbers or mass concentrations or with any other measurements over the whole sampling period.…”
Section: Msamentioning
confidence: 72%
“…In all PMF runs (unless mentioned otherwise), we used the high-resolution mass spectra for HOA and COA (cooking OA) from Crippa et al (2013b) as constraints, i.e. two rows of f k,j were set equal to the mass spectra of HOA and COA.…”
Section: General Principlementioning
confidence: 99%
“….04 in HOA and COA factor profiles (HOA based on Aiken et al, 2009;Mohr et al, 2012;Crippa et al, 2013bCrippa et al, , 2014, and COA based on Crippa et al, 2013bCrippa et al, , 2013cMohr et al, 2012); 2. f C 2 H 4 O + 2 <0.004 and 0.01 in HOA and COA, respectively (HOA based on Aiken et al, 2009;Mohr et al, 2012;Crippa et al, 2013bCrippa et al, , 2014, and COA based on Crippa et al, 2013bCrippa et al, , 2013cMohr et al, 2012) The first two criteria (1-2) ensure an appropriate separation of HOA and COA from OOA and BBOA, respectively. Criteria 3-5 relate to the evaluation of the correlation between factor and marker time series.…”
Section: Solution Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past years, source apportionment using high time resolution OA mass spectra measured by an aerosol mass spectrometer (AMS) or an aerosol chemical speciation monitor (ACSM) has been a useful approach to reduce the dimensionality of complex organic 15 fractions into more easily interpretable OA factors (e.g. Ulbrich et al, 2009;He et al, 2010;Ng et al, 2011;Crippa et al, 2013;Bougiatioti et al, 2014;Lee et al, 2015). Three primary factors: hydrocarbon-like organic aerosol (HOA), cooking organic aerosol (COA), and biomass burning organic aerosol (BBOA), are commonly identified in many locations.…”
mentioning
confidence: 99%